Relationship among the quality of cognitive abilities, depression symptoms, and various aspects of handgrip strength in the elderly - Jovanović Stevan S.; Trajkov Marija T.; Dopsaj Milivoj J.; Arsić Slađana D.; Milošević Radovan Lj.; Stojanović-Jovanović Biljana N.; Pavlović Dragan M. (Vojnosanitetski Pregled)
Background/Aim. Both the cognitive and physical functioning changes occur within the normal aging, suggesting possible common biological processes. The aging process is often characterized by a reduction of adaptive responses, an increasing vulnerability and functional limitations. The aim of this study was to determine if there were correlations between particular cognitive abilities (verbal ability, spatial ability, processing speed, memory, verbal fluency, divergent thinking, memory, attention, executive functions, conceptualization, orientation, computation), depression symptoms and different dynamometric parameters of muscle contraction, during handgrip (HG) of both hands, in the elderly population. Methods. The sample consisted of 98 participants, 16 males and 82 females, aged from 65 to 85. Neuropsychological assessment included Montreal Cognitive Assessment (MoCA), Frontal Function Test (Go/No-Go), Categorical and Phonemic fluency tests and Geriatric Depression Scale Short Form (GDS-SF). Physical measures were assessed by Handgrip Dynamometry Tests (HG), and included: the maximum force (Fmax), maximal rate of force development (RFDmax), static endurance HG time realized at 50% of maximal HG force (tFmax50%) of dominant (Do) and non-dominant (NDo) hand. Results. Higher MoCA score was followed by higher values of muscle endurance of dominant hands. Higher values of F max of dominant hand were associated with higher values of Alternating Trail Making that is by visuoconstructive abilities (MoCA). The variable Categorical fluency was in a small, positive correlation with Fmax. No correlation of depressive symptoms with HG parameters was found except in the subgroup of female subjects. Conclusion. Better cognitive performance was associated with better HG muscle strength. Therefore, HG strength can be a useful tool in geriatric practice in monitoring not only physical, but also cognitive function status and de-cline. The link between lower cognitive functioning and lower values of HG variables, emphasize the need for in-creased awareness about it in clinical practice.